(3GdaQhb Hjf GdJdGejP CHfGA GdeJhGabGJ RhGLjB h ZjQ GdeJhGabGJ RhGLjB aj HYV GdeJZjQGJ GdfaSjI (B/ s - (3ZGOI CMeO QLGFj GdWMdGhjs; (3YdGA GdOjf CMeO caGaj (B: s; (3eUWai CMeO JQcj (B: s ((3GdbGgQI (B: s (3ZGOI CMeO QLGFj GdWMdGhj (B: s, 2012)
(3gOaJ GdOQGSI Edi GdJYQa Ydi GdaQhb Hjf GdJdGejP CHfGA GdeJhGabGJ RhGLjB h ZjQ GdeJhGabGJ RhGLjB aj HYV GdeJZjQGJ GdfaSjI(B: (3h JhYjI h JHUjQ GdBHGA h GdCegGJ aj eLJeYfG GdeUQj HCgejI JCKjQ JhGabge GdRhGLj Ydi GdCHfGA(B: (3EP jMbb ddCHfGA eSJhi eQJaY ef GdJhGab GdfaSj GdeTQhW HGdJhGab GdRhGLj(B: (3EP jLYd GdCNjQ EMSGS GdWad HGdCef GdfaSj(B: (3h JbOjQg dPGJg(B: (3h KHGJg GdGfaYGdj(B: (3eeG jSGYOg Ydi GdJcja GdEjLGHj eY eLJeYg(B: (3h jfYcS CKQg Ydi MjGI GdWad OQGSjB h GLJeGYjB(B: (3h hLOGfjBs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ GdJQHhjI (B- (3bSe GdEQTGO GdfaSi hGdJQHhis
(3UOQ GjVG cbQU eOeLs
Keywords: (3CHfGA GdeJhGabGJ RhGLjB h ZjQ GdeJhGabGJ RhGLjB s; (3GdaQhb Hjf GdJdGejP s; (3GdeJZjQGJ GdfaSjI s